PERENCANAAN GAPURA DI KAWASAN MCK TERPADU JL. TIRTARONA RT 03, RW 07, KELURAHAN TLOGOMAS, KECAMATAN LOWOKWARU, KOTA MALANG - Agustina Nurul Hidayati; Mohammad Reza; Fardiah Qonita; M. Dafa Murtado; Andhyka Putra B; Utas Satrio Pangintan; Evan Evan (UNHI Press, 2020)
The gate as an identity in an area can be a center for depicting partnerships between the Tirtarona Foundation as a tour manager caring for changes in the Integrated Sanitation area with the National Institute of Technology Malang as a university in the field of technology that can enable to introduce the seriousness of the National Institute of Technology in developing technology in seeking the vision of the National Institute of Technology Malang to the community. For this reason, in the community service program we hope to provide a choice of the concept of the gate that will be built in the Integrated Sanitation Area.